THE PRINCIPLE OF ZAKAT, INFAQ, AND SHADAQAH ACCOUNTING BASED SFAS 109 - Habib, Anang Ariful (Universitas Negeri Malang, 2016)
The purpose of this research was to determine whether PSAK 109 about accounting of zakat, infaq and shadaqah that made by the government together with IAI that used as guidelines for the preparation of financial statement on the organization of zakat has been applied to the Amil Zakat, infaq and Shadaqah Agency (BAZIS). This research is the study of literature review in which the emphasis will be on the use of secondary data. Stages in this study, namely: formulating the problem, look for sources of literature that discusses the topic under study, evaluating the data, and analyze with interpret. Results from the study showed that most BAZIS in making financial report has not been guided by PSAK 109, which is still a lot of companies that use financial simple reporting with basic cash method, where in the recording of all transactions is only done when issuing and receiving cash.Keywords: accounting of zakat, infaq and shadaqah, PSAK 109, BAZIS